Critical Components for Spontaneous Activity and Rhythm Generation in Spinal Cord Circuits in Culture - Buntschu, Samuel; Tscherter, Anne; Heidemann, Martina; Streit, Jürg (Frontiers in Cellular Neuroscience, 2020)
Neuronal excitability contributes to rhythm generation in central pattern generating networks (CPGs). In spinal cord CPGs, such intrinsic excitability partly relies on persistent sodium currents (INaP), whereas respiratory CPGs additionally depend on calcium-activated cation currents (ICAN). Here, we investigated the contributions of INaP and ICAN to spontaneous rhythm generation in neuronal networks of the spinal cord and whether they mainly involve Hb9 neurons. We used cultures of ventral and transverse slices from the E13–14 embryonic rodent lumbar spinal cord on multielectrode arrays (MEAs). All cultures showed spontaneous bursts of network activity. Blocking synaptic excitation with the AMPA receptor antagonist CNQX suppressed spontaneous network bursts and left asynchronous intrinsic activity at about 30% of the electrodes. Such intrinsic activity was completely blocked at all electrodes by both the INaP blocker riluzole as well as by the ICAN blocker flufenamic acid (FFA) and the more specific TRPM4 channel antagonist 9-phenanthrol. All three antagonists also suppressed spontaneous bursting completely and strongly reduced stimulus-evoked bursts. Also, FFA reduced repetitive spiking that was induced in single neurons by injection of depolarizing current pulses to few spikes. Other antagonists of unspecific cation currents or calcium currents had no suppressing effects on either intrinsic activity (gadolinium chloride) or spontaneous bursting (the TRPC channel antagonists clemizole and ML204 and the T channel antagonist TTA-P2). Combined patch-clamp and MEA recordings showed that Hb9 interneurons were activated by network bursts but could not initiate them. Together these findings suggest that both INaP through Na+-channels and ICAN through putative TRPM4 channels contribute to spontaneous intrinsic and repetitive spiking in spinal cord neurons and thereby to the generation of network bursts.